Smoking–Thrombolysis Relationship Depends on Ischemic Stroke Subtype. Issue 7 (July 2016) - Tong, Xu; Wang, Chunjuan; Liao, Xiaoling; Pan, Yuesong; Yan, Hongyi; Cao, Yibin; Liu, Liping; Zheng, Huaguang; Zhao, Xingquan; Wang, Chunxue; Li, Hao; Wang, David; et al.
Abstract : Background and Purpose—: The relationship between smoking and the outcome in patients received thrombolysis is undetermined. The outcome could be influenced by different stroke subtypes. This study aimed to explore whether smoking had any impact on the outcome in patients with stroke of different subtypes who received intravenous thrombolysis. Methods—: All patients who received intravenous thrombolysis within 4.5 hours after symptom onset from the Thrombolysis Implementation and Monitor of Acute Ischemic Stroke in China (TIMS-China) database were eligible to be entered into this analysis. Smokers were considered if they smoked at least 1 cigarette/d for >6 months before stroke. Ischemic stroke subtype was classified by using the Trial of Org 10172 in Acute Stroke Treatment criteria. Outcome measurements included post–intravenous thrombolysis symptomatic intracranial hemorrhage within 7 days, mortality, and functional independence at 90 days. The relationship between smoking and thrombolysis was analyzed by using univariate and multivariate logistic regression models. Results—: Of 1118 patients enrolled, we identified 454 smokers and 664 nonsmokers. After stratifying for ischemic stroke subtypes, multivariate analysis revealed a significant relationship between smoking and functional independence in patients with noncardioembolism stroke subtypes (large artery atherosclerosis: odds ratio [OR], 1.452; 95% confidence interval [CI], 1.053–2.264; small artery occlusion: OR, 4.275; 95% CI, 1.098–16.649; other: OR, 3.120; 95% CI, 1.162–8.373). Furthermore, smoking was specially related to lower rates of symptomatic intracranial hemorrhage (OR, 0.316; 95% CI, 0.120–0.832) and mortality (OR, 0.272; 95% CI, 0.128–0.577) in patients with large artery atherosclerosis subtype. Conclusions—: In patients treated with intravenous thrombolysis, smoking could be related to a better chance of functional independence if their subtype of stroke was noncardioembolic, and a lower risk of symptomatic intracranial hemorrhage and mortality in those with large artery atherosclerosis. Abstract : Supplemental Digital Content is available in the text.